Cloud Computing in Bioinformatics: Solution to Big Data Challenge - Tufail, Shahid; Abdul Qadeer, M (International Journal of Computer Sciences and Engineering, 2025)
The piling up of vast quantity of biological data owing to the enormous exploitation of next and third generation sequencing techniques has made their management and handling an uphill task. Cloud computing offers solution to the storage, processing and analysis issues of such a gigantic amount of biological data. The abstraction layer in cloud computing empowers an incorporated access to handling, storage and virtualization. Herein, we review various types of clouds, cloud based service models in bioinformatics and cloud computing platforms with parallel application tools. Lastly, we discuss how the cloud based platforms are being exploited for big data analysis in biology.